Work Discipline and Emotional Intelligence: Impact on Employee Performance - Novalien Carolina Lewaherilla; Asiani Sijabat; Victor Huwae (Sean Institute, 2026)
This study aims to empirically test the effect of work discipline and emotional intelligence on employee performance at J&T Kebun Cengkeh Ambon. The independent variables in this study are work discipline and emotional intelligence, and the dependent variable is employee performance. The sampling technique used a simple saturated sampling technique, with a sample size of 36 people. Data analysis used is multiple linear regression test, descriptive statistical analysis, validity and reliability test, classical assumption test including normality test, multicollinearity test, and heteroscedasticity test with the help of SPSS 27. The results of this study indicate a significant effect of emotional intelligence on employee performance and there is no significant effect of work discipline on employee performance. The results of the F test found that work discipline and emotional intelligence jointly influence employee performance.